Efeito e custos do programa de tratamento estratégico seletivo no controle de ectoparasitoses e hemoparasitoses em bezerras leiteiras - Barbieri, Jonata de Melo (2015)
The objective of this study was to evaluate and estimate the actual cost of operating a selective strategic treatment program in control of ectoparasites, such as ixodidose (Rhipicephalus microplus) and myiasis caused by Dermatobia hominis ("warble") and Cochliomyia hominivorax ("screwworm) and blood parasites such as Anaplasma and Babesia spp. in dairy calves from birth to 12 months of age. This study was conducted in the Palmital Farm, Federal University of Lavras (UFLA), located in the municipality of Ijaci, MG, from April 2013 to November 2014. Thirty calves of Holstein were equally divided into two groups: G1) Treatment selective strategic (TE), and G2) conventional treatment (TC). The cost between the two treatments (TE x TC) was evaluated. In the statistical analysis we used the statistical package SAS and SPSS 18.0. The frequency of changes in physical parameters was higher (p <0.05) in TC compared to TE, between the seasons and the age of the calves. There was a significant triple interaction (p <0.05) related to the averages of tick counts, and in the warmer and wet season in both treatments, the counts were higher (28.55 - 23.21 and TC - TE). In the indirect immunofluorescence assay (IFA), to be positive for A. marginale and Babesia bovis was 85.6% and 87.8% (TE) and 83.2% and 83.2% (TC), respectively. The TE and TC groups showed a concentration of the number of cases of anaplasmosis subclinical (asymptomatic) in July (dry season). There was no significant difference in average daily gain between the TE and TC calves in the different age groups (0-90 days; 91-180 days and 181-365 days). The TE expenditures were 3.55 times greater than the TC, with average daily spending per pet of R$ 0.69 and R$ 0.19, respectively. The TE was more effective in controlling ectoparasites and blood parasites compared to conventional treatment (TC). Despite higher costs, the TE was effective in reducing the parasite burden, which positively reflected on the mortality rate of baby calves between the two treatments (TE = 0% and TC = 20%). The TE did not affect the dynamics of infection for A. marginale and B. bovis, and the Palmital Farm can be characterized as enzootic stability area for bovine anaplasmosis and babesisose. However, there was no significant difference (p> 0.05) in average daily gain weight (GPD) between the TE (0.58 kg) and the TC (0.57 kg), below the expected for heifers breed Dutch (0.80 kg), reflecting negatively on the projected age at first service (19 months). Thus, although the dairy property has to gain control of ectoparasites and hemoparasitoses, before deploying selective strategic program (TE), one should pay special attention to the nutritional plan of heifers, for animals reach the weight gain expected, reducing the age at first calving.